VATIS update : ozone layer protection. Vol. 4, No. 122, Jan-Feb 2014 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2014)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Scientists reveal new results from inside the ozone hole -- India and UNEP organize workshop for spare parts dealers -- Researchers develop a catalyst to destroy CFCs -- German carmakers make air conditioning breakthrough -- Water-based heat sealing and heat activation coating -- Engineered clean agent systems for larger environments -- Foam blowing agent technology for superior insulation -- Scientists study organic alternatives to soil fumigants THE SCIENCE OF OZONE LAYER . 4 -- Mercury and ozone depletion events in the Arctic -- Scientists reveal new results from inside the ozone hole -- NASA says ozone hole is stabilizing -- Researchers examined the beginning of ozone layer recovery ODS PHASE-OUT IN INDIA . 6 -- -- India and UNEP organize workshop for spare parts dealers -- Progress on the implementation of HPMP IN THE NEWS . 7 -- A drive towards natural refrigerants -- Sri Lanka to keep a check on ozone-depleting substances -- UNIDO helps China convert AC production to R290 -- Training programme on good practices in the servicing sector -- Plasma arc destruction system for Canadian fridge recycling firm -- Researchers develop a catalyst to destroy CFCs -- Permission for import-export of ozone-depleting substances -- Indonesia optimistic about slashing HCFC use by 97.5% -- Research findings on low-global warming refrigerants REFRIGERATION/AIR-CONDITIONING . 10 -- German carmakers make air conditioning breakthrough -- New refrigeration technology to cool drinks -- New Hybrid ground source heat pump -- Using CO2 to reduce carbon footprint -- CO2 compressor unit for ice arenas -- Safety tests for Mercedes CO2 refrigerant SOLVENTS . 12 -- New precision cleaning agent -- US to ban HCFC 225 production ...